(untitled) (Journal of Hama University, 2025)
This study aimed to recognize The level of school administration, practice of the first cycle of basic education in the development the values of citizenship among pupils from the point of view of six class pupils in the city of Lattakia, and to recognize the difference between the averages of the responses the pupils on the questionnaire according to the variable of gender, to achieve the aim of the study, the research developed a questionnaire included (39) sentences, and she applied on a random sample of (427) students. the study introduced recommendations about the role of school administration. By depending on the suitable statistic ways and using the approach of synthesis, the study found that the role of school administration in the development of values of citizenship among pupils from the point of view of pupils of the first cycle of basic education was high level, the role of school administration in the development of duties was the first, then rights, then belonging. the results have showed differences the averages of the responses the pupils on the questionnaire according to the variable of gender.